2019
DOI: 10.3390/w11030622
|View full text |Cite
|
Sign up to set email alerts
|

On the Connection between Atmospheric Moisture Transport and Dry Conditions in Rainfall Climatological Zones of the Niger River Basin

Abstract: The hydroclimatology of the Niger River basin, located in West Africa, is very complex. It has been widely studied because of its importance to the socioeconomic activities of the countries that share its natural resources. In this study, to better understand the causes and mechanisms that modulate the rainfall over the Niger River basin, we identified the most relevant moisture sources for precipitation within the basin. The Lagrangian model FLEXPART was utilised to track backward trajectories of air parcels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…Despite the method dependence on the results, the adequacy of the methodology to investigate the hydrological cycle is supported on the multiple previous works in which it was applied (e.g., Nieto et al ., 2014; Gimeno et al ., 2016; Ramos et al ., 2016; Drumond et al ., 2019). Specifically, the methodology here implemented has been previously utilised for investigating the hydrological cycle in tropical monsoonal regions such as the Amazonia (Drumond et al ., 2014; Sorí et al ., 2018), West Africa (Nieto et al ., 2006; Sorí et al ., 2019), and south Asia (Ordoñez et al ., 2012; Sorí et al ., 2017).…”
Section: Datasets and Methodologymentioning
confidence: 99%
“…Despite the method dependence on the results, the adequacy of the methodology to investigate the hydrological cycle is supported on the multiple previous works in which it was applied (e.g., Nieto et al ., 2014; Gimeno et al ., 2016; Ramos et al ., 2016; Drumond et al ., 2019). Specifically, the methodology here implemented has been previously utilised for investigating the hydrological cycle in tropical monsoonal regions such as the Amazonia (Drumond et al ., 2014; Sorí et al ., 2018), West Africa (Nieto et al ., 2006; Sorí et al ., 2019), and south Asia (Ordoñez et al ., 2012; Sorí et al ., 2017).…”
Section: Datasets and Methodologymentioning
confidence: 99%
“…It has shown that the moisture supply for heavy rainfall events is primarily driven by moisture transportation rather than local evaporation (Trenberth et al, 2003). Consequently, there has been a growing interest in identifying the moisture sources for rainfall events in recent decades (Dominguez et al, 2006;Rapolaki et al, 2021), spanning Europe (Keune & Miralles, 2019;Sodemann & Zubler, 2009;Winschall et al, 2014aWinschall et al, , 2014b, America (Dur an-Quesada et al, 2017;Hoyos et al, 2018), Africa (Nieto et al, 2006;Sorí et al, 2019) and Asia (Bohlinger et al, 2017;Martius et al, 2013;Zhang et al, 2019aZhang et al, , 2022. Surrounded by oceans on all three sides and influenced by the northern East Asian monsoon, South Korea is particularly susceptible to hydro-climatological extremes (Ahn & Ahmad Nayak, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Observed association of extreme rains with high moisture (e.g., Khodayar et al 2018, Grazzini et 2020 supports this belief. As a result, the question of rain formation, to be studied by itself (Pruppacher andKlett 1997, Khain andPinsky 2018), is often reduced to that of tracing a moisture source (e.g., Trenberth 1998, Sorí et al 2019.…”
Section: Introductionmentioning
confidence: 99%